Factors Affecting External Audit Fee: A Survey of Mining Sector Companies in Indonesia - Nazara, Arizaro; Rusmanto, Toto (Journal of World Science, 2022)
Introduction: This study aims to examine the effect of Profitability, Company Complexity, Audit Committee, Public Accounting Firm Size, Company Risk, and Company Size on External Audit Costs. Method: The samples used in this study were 23 mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The sampling technique used was a purposive sampling method. Secondary data in this study is based on Annual Reports published on the official website of the IDX and the official website of the sample companies. Result: The results of this study indicate that the significance value is 0.000, which means it is smaller than 0.05 (0.000 <0.05), and the calculated F is greater than the F table (16.981> 2.1837), so that it is obtained that simultaneously or together -the same independent variables (profitability, complexity) of the company, audit committee, KAP size, company risk, and company size) have a significant effect on the dependent variable (external audit fees). Conclusion: (1) Profitability has no effect on External Audit Costs, (2) Company complexity has a significant positive effect on External Audit Costs, (3) Audit Committee has no effect on External Audit Costs, (4) Size of the Public Accounting Firm has a significant positive effect. Against External Audit Costs, (5) Company Risk does not affect External Audit Costs, and (6) Company Size has a significant positive effect on External Audit Costs.